2022
DOI: 10.1021/acsomega.2c00365
|View full text |Cite
|
Sign up to set email alerts
|

Glass Fiber–Epoxy Composites with Boron Nitride Nanotubes for Enhancing Interlaminar Properties in Structures

Abstract: Hybrid composite materials are a class of materials where more than one type of reinforcement is integrated into a matrix to achieve superior properties. This typically involves nanoparticle fillers employed within traditional advanced composites with fiber reinforcements such as carbon or glass. The current study builds on previous investigations of boron nitride nanotube (BNNT) hybrid composites, specifically glass fiber (GF)–epoxy/BNNT composite laminates. GF is an effective and affordable primary reinforce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Carbon nanotubes (CNTs) offer many advantages in the construction of new materials. 27,28 They have unique and interesting properties such as mechanical, electrical, optical, and magnetic properties, which can be tuned to some extent. CNTs can improve the mechanical and electrical properties of materials, making them suitable for applications in strengthenhanced structural materials, wearable thermoelectric devices, smart textiles, and flat panel displays.…”
Section: Addition Of Cnts To Compositesmentioning
confidence: 99%
See 1 more Smart Citation
“…Carbon nanotubes (CNTs) offer many advantages in the construction of new materials. 27,28 They have unique and interesting properties such as mechanical, electrical, optical, and magnetic properties, which can be tuned to some extent. CNTs can improve the mechanical and electrical properties of materials, making them suitable for applications in strengthenhanced structural materials, wearable thermoelectric devices, smart textiles, and flat panel displays.…”
Section: Addition Of Cnts To Compositesmentioning
confidence: 99%
“…Carbon nanotubes (CNTs) offer many advantages in the construction of new materials 27,28 . They have unique and interesting properties such as mechanical, electrical, optical, and magnetic properties, which can be tuned to some extent.…”
Section: Introductionmentioning
confidence: 99%
“…ML approaches are useful for evaluating large data sets, predicting material behavior, improving composite qualities, and speeding up the creation of novel materials. 40,41 By identifying the optimal mix of fibers, epoxy resin, and other additives, ML algorithms can aid in the design and optimizing FRECs. These algorithms may examine material attributes, processing circumstances, and cost limitations to recommend formulations that satisfy specific needs.…”
Section: Introductionmentioning
confidence: 99%
“…Al-Zubaydi et al 31 studied the effect of nano TiO 2 particles on the properties of carbon fiber-epoxy composites and showed improved mechanical and wear resistance properties with the addition of 4% TiO 2 . Vaddar et al 32 investigated glass fiber-epoxy composites with carbon nanotube fillers for enhancing properties in structure modeling and analysis using artificial intelligence technique, and the results revealed that a load of 1.005 kg, a sliding velocity of 1.499 m/s, a sliding distance of 150 m, and 15 wt % of filler were found to be the optimal parameters for the efficient reduction of specific wear rate. Navaneeth et al 33 investigated "Damped Free Vibration Analysis of Woven Glass Fiber-Reinforced Epoxy Composite Laminates" which showed a good agreement.…”
Section: Introductionmentioning
confidence: 99%